HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERILAKU TEMPER TANTRUM PADA ANAK USIA TODDLER DI DESA KALIBUKBUK: HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERILAKU TEMPER TANTRUM PADA ANAK USIA TODDLER DI DESA KALIBUKBUK - Ari Pertama Watiningsih; I Dewa Ayu Rismayanti; Ni Nyoman Sriastiyani (LPPM STIKes Buleleng, 2018)
Introduction Temper Tantrum is an explosive and uncontrollable emotional overflow where when a child shows a negative attitude or rejection that is expressed by crying, screaming, throwing objects, rolling around until they hit. Parenting Parenting is a pattern of parental behavior in children, where parents give encouragement to children, by changing behavior, knowledge, and values ​​that are considered most appropriate for parents so that children can be independent. Purpose: This study aims to determine the relationship of parenting parents to temper tantrum behavior in toddler age children in Kalibukbuk Village. Method: The research design used was correlational analytic with cross-sectional design. The sample used as many as 32 samples were selected by probability sampling technique, simple random sampling. Data collection was carried out using a questionnaire. Results: Data analysis showed that as many as 14 children (43.8%) had moderate tantrum temper and 13 children (40.6%) had high temper tantrum. A total of 21 people (65.6%) had a parenting pattern that tended to be authoritarian, while permissive parenting had 7 people (21.9%). Spearman rank test results obtained p value of 0.01 (<0.05) indicating the relationship between parents and temper tantrum.